2019
DOI: 10.1108/ijhcqa-07-2017-0116
|View full text |Cite
|
Sign up to set email alerts
|

Business process improvement methods in healthcare: a comparative study

Abstract: Purpose According to the literature concerned with this study, less than satisfactory outcomes have been achieved through implementing business process improvements methods (BPIMs) in industries, in general, and in healthcare, in particular. The existing methods used need to be enhanced in order to create more effective outcomes. There has also been a lack of studies documenting gaps or shortfalls in implementing BPIMs, to be presented to the BPI research community. Therefore, researchers of this paper have at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
0
15
0
1
Order By: Relevance
“…This importance has been pointed out by other studies [134,[161][162][163][164]. Other common tools include standard work, i.e., a concept whereby each work activity is precisely described with a specific cycle time, task sequence, and other steps involved within the process [95], and is considered a prerequisite for flow [10]; the 5'S program, which is used to eliminate clutter [165] and enhance the standardization of stock, as well as to systematically organize the unit and streamline the documentation processes [97]; cause and effect analyses, which are used to map the possible causes of a problem into categories [90,166]; and Kaizen, which is a philosophy of continuous incremental improvement over time and space [29,99,104]. These findings are similar with those reported in previous studies [44,62,161], and sustain the assertion that most LH interventions focus more on tools related to assessment and improvement and less on processes-monitoring tools.…”
Section: Lean Healthcarementioning
confidence: 99%
“…This importance has been pointed out by other studies [134,[161][162][163][164]. Other common tools include standard work, i.e., a concept whereby each work activity is precisely described with a specific cycle time, task sequence, and other steps involved within the process [95], and is considered a prerequisite for flow [10]; the 5'S program, which is used to eliminate clutter [165] and enhance the standardization of stock, as well as to systematically organize the unit and streamline the documentation processes [97]; cause and effect analyses, which are used to map the possible causes of a problem into categories [90,166]; and Kaizen, which is a philosophy of continuous incremental improvement over time and space [29,99,104]. These findings are similar with those reported in previous studies [44,62,161], and sustain the assertion that most LH interventions focus more on tools related to assessment and improvement and less on processes-monitoring tools.…”
Section: Lean Healthcarementioning
confidence: 99%
“…The hospital aimed to increase the IV-tPA administration rate and Endovascular Therapy (EVT) rate (transfers to another hospital) by reducing the Door-to-CT and Door-to-Needle lead time activities. Recently, Ahmed et al (2019) noted that Six Sigma, Lean and Lean Six Sigma are among the most commonly used methodologies for improvement in healthcare. In the BPMC case, the decision to combine lean and six sigma is consistent with the modern research direction to combine more quality improvement methods to create stronger and more sustainable results (Ahmed et al, 2019).…”
Section: Methodology and Case Study Designmentioning
confidence: 99%
“…For instance, Bhat and Jnanesh (2014) demonstrated that the LSS implementation in a rural hospital in India produced a reduction in cycle time of out-patient department services. Similarly Ahmed et al (2019) pointed out that LSS and workforce management have a significant impact on quality performance of the Malaysian hospitals. Concerning the six sigma, Prajapati and Suman (2019) presented a successful application aimed to reduce the length of stay for neonatal jaundice patients in an Indian rural hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Business Process Improvement (BPI) sangat erat kaitannya dengan perbaikan pada pengelolaan aktivitas atau proyek untuk mendapatkan hasil yang lebih optimal. Pengelolaan aktivitas atau proyek yang baik pada lingkungan bisnis merupakan suatu hal yang penting karena hal ini dapat meningkatkan tingkat keberhasilan aktivitas/proyek dan memberikan jaminan yang lebih besar kepada stakeholder terkait dengan pengelolaan sumber daya secara efektif [1][2] [3]. Pada Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi) Vol.…”
Section: Pendahuluanunclassified